The Secrets of Winterhouse - Guterson, Ben (Guterson, Ben. Winterhouse trilogy, 2020)
Back at the Winterhouse hotel for another holiday season, Elizabeth and Freddy, who love puzzles, dig deeper into the mystery surrounding a hotel guest who left behind odd artifacts, including a magical book that evil Gracella Winters once attempted to use to gain destructive power over the entire Falls lineage.